Contamination characteristics, coexistence relationships and health risk assessment of dioxins and metals in topsoil around municipal solid waste incinerator in Hainan, China - Tang, Ling; Guo, Jing; Li, Ling; Wan, Ruxing; Cui, Lei; Liu, Aimin; Lu, Yong (Frontiers in Environmental Science, 2022)
Highly toxic pollutants such as dioxins and metals emitted from municipal solid waste (MSW) incineration have caused a serious not-in-my-backyard social phenomenon. However, relatively few studies have comprehensively analyzed the contaminant characteristics, coexistence relationships and potential health risks of dioxins and metals in soils near MSW incinerator. Therefore, this study monitors 17 dioxin homologues and 13 metals in soils around MSW incinerator to evaluate their contaminant and coexistence characteristics as well as associated potential health risks. The empirical study focused on Hainan Province, a relatively pure area with no heavy industry and low population density in southern China. The contamination characteristics analysis shows that the total International Toxic Equivalence Quantity (I-TEQ) concentrations of dioxins are comparatively lower than the risk control standards and that in previous studies, whereas the concentrations of specific metals (e.g., Ni, Cu, Cd and Cr) are higher than the risk control standards. To explore the coexistence relationships, the statistical analysis is conducted and indicates that Sb, Cd, Zn and Pb metals (extracted as principal components, with a variance contribution rate of 30.89%) and most dioxin homologues (accounting for 82.83% of the total I-TEQ values) are clustered into one group, suggesting that they may have similar distribution characteristics and origins. Furthermore, the health risk analysis of two toxic pollutants reveals that the carcinogenic and non-carcinogenic risks of dioxins and most metals (except for Ni and Cr) are all below the acceptable levels, implying that the studied incinerator posed no obvious health effect to the surrounding residents.